Humor Styles as Moderators in the Relationship Between Perceived Stress and Physical Health. (June 2017) - Richards, Kirsten; Kruger, Gert
This study examined the moderating role of four humor styles, namely, self-enhancing, affiliative, self-defeating, and aggressive humor, in the relationship between perceived stress and physical health. The sample comprised 954 undergraduate students of both genders between the ages of 18 and 43 years ( M = 20 years) from various ethnic backgrounds (68.2% Black African, 19.1% White, 7.3% Colored, and 5.3% Indian). Three self-report measures were administered to assess humor styles, perceived stress, and physical health. Results showed that the self-defeating humor style moderated the relationship between stress and physical health with higher use of this humor style associated with an increase in reported physical health symptoms. The results highlight the role of a self-directed, detrimental humor style in the deterioration of physical health during the perceived experience of stress, thus indicating that one's habitual way of using humor could influence whether physical health outcomes are positive or negative.